Malaysian teachers' attitude, competency and practices in the teaching of thinking. - Hashim, Rosnani (IIUM Press, 2003)
The development of the third wave of Information and Communication Technology is accompanied by the growing concern of the decline of an individual's ability to think sharply and wisely. In Malaysia, this concern has brought to fore the prominence of teaching thinking skills within the school system and teachers were expected to be the agents of this change. Are teachers aware of the importance of this thinking ability? Have they been adequately prepared for this paradigm shift? Do they personally feel competent teaching for thinking in the classrooms? This survey attempts to answer these questions and investigates the relationship between teachers' attitude and practices. it also examines if there exists any significant differences in teachers' beliefs and their practices with respect to gender, course attendance and teaching experience. Finally, it explores some of the problems faced by teachers in teaching for thinking.